2023
DOI: 10.3389/fphar.2023.1234300
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel human triculture model of non-alcoholic fatty liver disease and identification of berberine as ameliorating steatosis, oxidative stress and fibrosis

Hossein Rafiei,
Michelle Yeung,
Sara Kowalski
et al.

Abstract: Objectives: Non-alcoholic fatty liver disease (NAFLD) and its progression to non-alcoholic steatohepatitis (NASH) and hepatocarcinoma is a serious and growing problem. However, the development of new therapies is severely hindered by a lack of high-throughput assays for drug testing.Methods: We have developed a simple transwell assay comprised of HepG2 hepatocytes, hepatic LX-2 stellate cells, and differentiated THP-1 cells. The cells were incubated with an activating mixture containing the NASH-associated ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 53 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…Moreover, in cell cultures, BBR proved to have an effective anti-steatotic property, showing a decrease in the accumulation of lipids or an improvement in NAFLD-induced changes in different cell lines. In the last few years, researchers have been keen to find the relationship between different inflammatory pathways and their contribution to NAFLD's progression [138]. Some studies we analyzed found that mitochondria may play a more significant role in stress oxidative response than was known.…”
Section: Pre-clinical Studies Of Berberine Effects In Experimental Mo...mentioning
confidence: 96%
“…Moreover, in cell cultures, BBR proved to have an effective anti-steatotic property, showing a decrease in the accumulation of lipids or an improvement in NAFLD-induced changes in different cell lines. In the last few years, researchers have been keen to find the relationship between different inflammatory pathways and their contribution to NAFLD's progression [138]. Some studies we analyzed found that mitochondria may play a more significant role in stress oxidative response than was known.…”
Section: Pre-clinical Studies Of Berberine Effects In Experimental Mo...mentioning
confidence: 96%